Smith predictor embedded with fractional algorithms for the control of a heat diffusion system - Jesus, Isabel S. (2009)
In this paper we study the control of a heat diffusion system based on the application of the fractional calculus concepts. In this perspective, several algorithms are investigated and compared, when integrated within a Smith predictor structure. Simulations are presented assessing the performance of the proposed fractional algorithms.